A comprehensive study of olefin metathesis catalyzed by Ru-based catalysts - Albert Poater; Luigi Cavallo (Beilstein Journal of Organic Chemistry, 2015)
During a Ru-catalyzed reaction of an olefin with an alkylidene moiety that leads to a metallacycle intermediate, the cis insertion of the olefin can occur from two different directions, namely side and bottom with respect to the phosphine or N-heterocyclic ligand (NHC), depending on the first or second generation Grubbs catalyst. Here, DFT calculations unravel to which extent the bottom coordination of olefins with respect is favored over the side coordination through screening a wide range of catalysts, including first and second generation Grubbs catalysts as well as the subsequent Hoveyda derivatives. The equilibrium between bottom and side coordination is influenced by sterics, electronics, and polarity of the solvent. The side attack is favored for sterically less demanding NHC and/or alkylidene ligands. Moreover the generation of a 14-electron species is also discussed, with either pyridine or phosphine ligands to dissociate.